2020
DOI: 10.1128/msystems.00190-20
|View full text |Cite
|
Sign up to set email alerts
|

Bactopia: a Flexible Pipeline for Complete Analysis of Bacterial Genomes

Abstract: Sequencing of bacterial genomes using Illumina technology has become such a standard procedure that often data are generated faster than can be conveniently analyzed. We created a new series of pipelines called Bactopia, built using Nextflow workflow software, to provide efficient comparative genomic analyses for bacterial species or genera. Bactopia consists of a data set setup step (Bactopia Data Sets [BaDs]), which creates a series of customizable data sets for the species of interest, the Bactopia Analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 99 publications
(134 reference statements)
0
98
0
Order By: Relevance
“…2 ), lacking one or more domains. Also, the subtype II-C in CRI10 is probably a prediction artifact, as a single subtype with two sets of cas genes can be detected as multiple subtypes ( Crawley et al, 2018 ) and only the subtypes I-B, I-E, and II-A were reported for this species ( Petit & Read, 2020 ). The result suggests that the CRISPR-Cas systems are not functional due to gene fragmentation which could compromise the prevention of phage infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ), lacking one or more domains. Also, the subtype II-C in CRI10 is probably a prediction artifact, as a single subtype with two sets of cas genes can be detected as multiple subtypes ( Crawley et al, 2018 ) and only the subtypes I-B, I-E, and II-A were reported for this species ( Petit & Read, 2020 ). The result suggests that the CRISPR-Cas systems are not functional due to gene fragmentation which could compromise the prevention of phage infections.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic analyses have been performed to identify genomic features of L. crispatus associated with female urogenital tract using samples from North America, Europe and Asia ( Ojala et al, 2014 ; Abdelmaksoud et al, 2016 ; France, Mendes-Soares & Forney, 2016 ; Van der Veer et al, 2019 ; Pan, Hidalgo-Cantabrana & Barrangou, 2020 ; Petit & Read, 2020 ; Zhang et al, 2020 ). Analyses that searched for genomic features associated with lactobacilli-dominated (healthy) or BV microbiota were performed using samples isolated from the USA ( Abdelmaksoud et al, 2016 ) and Netherlands ( Van der Veer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…ezbiocloud. net/ tools/ ani) [28] revealed that the ANI values of strains NLN63 T and NLN82 were lower than the threshold (95-96 %) with other recognized species in genus Pelistega ( Table 2). Of note, the ANI value between strains NLN63 T and NLN82 was 98.1 %, above the threshold, indicating that they belong to the same species.…”
Section: Introductionmentioning
confidence: 99%
“…Overall genome relatedness indices, especially average nucleotide identity (ANI), have been increasingly used [23–27]. ANI calculation applied in this study to delineate species using the OrthoANIu algorithm (www.ezbiocloud.net/tools/ani) [28] revealed that the ANI values of strains NLN63 T and NLN82 were lower than the threshold (95–96 %) with other recognized species in genus Pelistega (). Of note, the ANI value between strains NLN63 T and NLN82 was 98.1 %, above the threshold, indicating that they belong to the same species.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous tools designed to address aspects of complete bacterial genome construction have been developed by both ONT and community users, however few pipelines exist that offer end-to-end construction of bacterial genomes. Currently, these include Katuali (ONT), CCBGpipe [4], ASA 3 P [5] and Bactopia [6]. Katuali is an ONT developed assembly pipeline implemented in Snakemake.…”
Section: Introductionmentioning
confidence: 99%